THE FACTORS OF CONSOLIDATION OF UKRAINIAN CHURCH ELITE: PARALLELS BETWEEN THE EARLY-MODERN AND CONTEMPORARY AGE - Kagamlyk, Svitlana (Київський національний університет імені Тараса Шевченка, 2017)
Modern Ukrainian reality requires not only a profound scientific analysis of postcolonial problems and the search for effective methods to overcome them, but also the experience of the Ukraine’s colonial past to make it impossible in the future. The research of the religious factor in the Ukrainian’s society integration has a rather long tradition, since the classical heritage of Metropolitan Ivan Ogienko, Mykhailo Hrushevsky, Metropolitan Andriy Sheptytsky, Dontsov, V. Lypynsky and others. Scientists emphasized the special role of the Church in the period of loss of Ukrainian statehood, when it largely took over the functions of state power. This is applying to the early modern era: at that time the representatives of the Ukrainian higher clergy were the creators of the national spirituality and culture, and played the role of the religious, church-political, cultural and intellectual wires of society. The aim of the article is to find out the factors that contributed or negatively influenced the process of consolidation of the church elite. The parallels between the early modern and modern era in the Ukraine’s history toward the processes that contributed to, or, conversely, complicated the process of uniting the ecclesiastical elite, testify to the reality of such analogies. In particular, the centrifugal tendencies in the Orthodox Church became negative factors for the consolidation of Orthodoxy in conditions of independence in the early modern days. At the end of the XVII century from the subordination of the Kyiv Metropolitan came out the Kyiv-Mezhygirsky monastery, the Kyiv-Pechersk Lavra and the Chernihiv diocese. An example of centrifugal tendencies in the Ukrainian Orthodox environment can be called the split in the 90's of the XX century to three different branches (UOC-KP, UOC-MP, UAOC). Another destructive factor in the process of the church elite consolidating was the conflicts of corporate interests between separate church institutions that took place in the early modern days (the dispute over printing between the Kyiv Metropolia and the Kyiv-Pechersk Lavra, land disputes between monasteries) and in the conditions of independence (different vision for the leadership of each of the Orthodox Churches of the principles of the unifying process). The author concludes that overcoming these problems is a prerequisite for the creation of a single Ukrainian Local Orthodox Church as the main idea of the Ukrainian people on the way to its real unity. Key words: Consolidation, Ukrainian church elite, Orthodox Church, Contemporary age, Destructive processes

У статті зроблено спробу з’ясувати чинники, які сприяли чи негативно впливали на процес консолідації церковної еліти ранньомодерного часу, і встановити паралелі з цими процесами в нашій сучасності. Зазначено, що сучасна українська дійсність вимагає глибокого наукового аналізу не лише проблем постколоніальної доби та пошуку ефективних шляхів для їх подолання, але й досвіду колоніального минулого України для його унеможливлення в майбутньому. Зроблено висновок, що проведені автором паралелі між ранньомодерною і сучасною добою в історії України щодо процесів, які сприяли, чи, навпаки, ускладнювали процес згуртування церковної еліти, засвідчують реальність таких аналогій. Зокрема, негативними факторами для консолідації православ’я в умовах незалежності, як і в ранньомодерну добу, стали відцентрові тенденції у середовищі Православної Церкви. Іншим деструктивним фактором у цьому контексті стали конфлікти корпоративних інтересів між окремими церковними інституціями, які мали місце як у ранньомодерну добу, так і в умовах незалежності. Подолання цих проблем є необхідною умовою створення єдиної Української Помісної Православної Церкви, як головної ідеї українського народу на шляху до його реальної єдності. Ключові слова: консолідація, українська церковна еліта, Православна Церква, ранньомодерна доба, деструктивні процеси
ЧИННИКИ КОНСОЛІДАЦІЇ УКРАЇНСЬКОЇ ЦЕРКОВНОЇ ЕЛІТИ: ПАРАЛЕЛІ МІЖ РАННЬОМОДЕРНОЮ І СУЧАСНОЮ ДОБОЮ